2020
DOI: 10.3390/en13153902
|View full text |Cite
|
Sign up to set email alerts
|

Value Co-Creation Behavior in Green Supply Chains: An Empirical Study

Abstract: As an important supply chain development strategy, green investment and sustainability are concerns of the government and enterprises. However, due to the high cost and low profit of green investment, a large number of small and medium-sized firms can be deterred from their implementation. Value co-creation has become a key measure to solve this problem. This article explores the relationship between the green supply chain (GSC) strategy, value co-creation, and corporate performance in the manufacturing enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 79 publications
(96 reference statements)
6
23
0
Order By: Relevance
“…The high cost and low profit of green investment are concerns for the government and enterprises deterred from their implementation of green investment. Shi et al [8] suggested that value co-creation has become a key measure to solve this problem. The green supply chain strategy can promote a high level of firms' value co-creation with their supply chain partners, and different value co-creation modes have different effects on firm performance.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The high cost and low profit of green investment are concerns for the government and enterprises deterred from their implementation of green investment. Shi et al [8] suggested that value co-creation has become a key measure to solve this problem. The green supply chain strategy can promote a high level of firms' value co-creation with their supply chain partners, and different value co-creation modes have different effects on firm performance.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…This Special Issue of Energies on the subject of "Green Energy Technology" contains the successful invited submissions [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. A total of 17 technical papers that cover diversified green energy technology-related research have shown critical results and contributed significant findings in biofuel production [1], energy-saving in buildings [2], wind energy [3], energy policy [4], electricity supply [5], a thermal-hydraulic system [6], fluidized bed reactor [7], green-supply chains [8], SI engine [9], renewable energy grid [10], kinetic energy harvest [11], green hydrogen utilization [12], water conservation [13], hydraulic power [14], Illumination Performance in buildings [15], community renewable energy [16], and heat transfer [17].…”
Section: Introductionmentioning
confidence: 99%
“…We can find that the first-order and second-order principals of the Hessian matrix are Then make the first-order partial derivative of the manufacturer's profit function with respect to 0, and combine the above formula to get the optimal decision: Lemma 2: According to formula (6), (7), (10) and (11), we know that the value of θ satisfied at…”
Section: Cost Sharing Modelmentioning
confidence: 99%
“…There are few literatures on value co-creation among enterprises, and they mainly focus on the value co-creation of manufacturers and suppliers. The core of value cocreation among enterprises is interdependence and mutual trust, forming a more complex customized relationship, then cooperation may bring higher value than independent companies [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Pimonenko et al (2020) [29,30]; Palma-Ruiz, Castillo-Apraiz, and Gomez-Martinez, (2020)[88];Cheng et al (2018) [75]; Aboulamer, (2018)[81]; Jazairy (2020)[66];Shi et al (2020) [93]; Xing, Xia, and Guo (2019)[7]; Yen (2018)[22];Zhang et al (2015) [6] Climate change Green investments are invariably combined with climate change mitigation or adaptation. Environmentally-friendly technologies significantly reduce pollution ( CO2 emissions and fuel consumption), the abatement cost being under environmental regulations.…”
mentioning
confidence: 99%